Characteristics of Palm Kernel Shell/Alumina/Epoxy Composites as Motorcycle Brake Pad Material - Mastariyanto Perdana; Meiki Eru Putra; Akmal Akmal; Hengki Putra; Murfid Al Ikram; Ardhy Meidianda (Jurnal Teknik Mesin, 2023)
Brake pads are one of the components of a motor vehicle that functions to slow down or stop the vehicle's motion. In the concept of braking, one inevitable factor is wear and tear. Wear and tear occur when two objects press against each other and create friction. Composite material is an alternative substance that can be used to replace asbestos brake pads. In this research, shell of palm oil, alumina (Al2O3) powder and epoxy was used for material of brake pad. Type of brake pads was made in this study is brake pads used for motorcycle disc brakes. Addition of volume fraction of alumina powder to 6% in composite material. The aims this study was determine the characterization of brake pad based on composite materials with addition of alumina powder in composite material. This study showed that there was increase of physical and mechanical properties with the addition of alumina powder in composites up 6% by volume fraction.